Analisis Penerimaan Penggunaan Fintech LinkAja sebagai Media Pembelian dan Pembayaran Transaksi Elektronik di Kota Denpasar - Kaniawati, Maya; Estiyanti, Ni Made; Redioka, Anak Agung Ngurah (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2024)
Technological developments in the digital era are currently making many innovations in the field of technology, one of which is the financial sector that presents digital-based financial services or known as fintech. The presence of fintech digital payment system services provides changes in digital wallet transactions, one of which is LinkAja. This research is intended to find out how the acceptance of the use of the LinkAja digital wallet in Denpasar City by applying the original model to the Technology Acceptance Model (TAM). This study uses descriptive statistical analysis with frequency distribution statistics and data analysis using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The sampling technique in this study used a purposive accidental sampling technique. The results of the tests carried out showed that of the 100 respondents studied, the results of the statistical analysis of the frequency distribution gave an assessment of agreeing on the ease of use, benefits of use, attitude of use, and the actual use of LinkAja products, which means that respondents considered LinkAja products easy to use, useful and the user shows a good attitude towards the product, and the user intends well to use the linkAja product. Keywords— Financial Technology, Digital Payment System, LinkAja, Technology Acceptance Model, Frequency Distribution, PLS